Adjuvant chemotherapy for stage III colon cancer: relative dose intensity and survival among veterans - Aspinall, Sherrie L (BMC Cancer, 2015)
BACKGROUND: Given the paucity of information on dose intensity, the objective of this study is to describe the use of adjuvant chemotherapy for stage III colon cancer, focusing on relative dose intensity (RDI), overall survival (OS) and disease-free survival (DFS). METHODS: Retrospective cohort of 367 patients diagnosed with stage III colon cancer in 2003–2008 and treated at 19 VA medical centers. Kaplan-Meier curves summarize 5-year OS and 3-year DFS by chemotherapy regimen and RDI, and multivariable Cox proportional hazards regression was used to model these associations. RESULTS: 5-fluorouracil/leucovorin (FU/LV) was the most commonly initiated regimen in 2003 (94.4%) and 2004 (62.7%); in 2005–2008, a majority of patients (60%-74%) was started on an oxaliplatin-based regimen. Median RDI was 82.3%. Receipt of >70% RDI was associated with better 5-year OS (p < 0.001) and 3-year DFS (P = 0.009) than was receipt of ≤70% RDI, with 5-year OS rates of 66.3% and 50.5%, respectively and 3-year DFS rates of 66.1% and 52.7%, respectively. In the multivariable analysis of 5-year OS, oxaliplatin + 5-FU/LV (versus 5-FU/LV) (HR = 0.55; 95% CI = 0.34-0.91), >70% RDI at the first year (HR = 0.58; 95% CI = 0.37-0.89) and married status (HR = 0.66; 95% CI = 0.45-0.97) were associated with significantly decreased risk of death, while age ≥75 (versus 55–64) (HR = 2.06; 95% CI = 1.25-3.40), Charlson Comorbidity Index (HR = 1.17; 95% CI = 1.06-1.30), T4 tumor status (versus T1/T2) (HR = 5.88; 95% CI = 2.69-12.9), N2 node status (HR = 1.68; 95% CI = 1.12-2.50) and bowel obstruction (HR = 2.32, 95% CI = 1.36-3.95) were associated with significantly increased risk. Similar associations were observed for DFS. CONCLUSION: Patients with stage III colon cancer who received >70% RDI had improved 5-year OS. The association between RDI and survival needs to be examined in studies of adjuvant chemotherapy for colon cancer outside of the VA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1038-y) contains supplementary material, which is available to authorized users.